Prenatal factors associated with fetal visceral adiposity - Aline Silva Santos Sena; Alex Sandro Rolland de Souza; Vivianne de Oliveira Barros; Maria do Carmo Pinto Lima; Adriana Suely Oliveira Melo; Melania Maria Ramos de Amorim (Brazilian Society of Pediatrics, 2020)
Objective: To assess fetal visceral adiposity and associated factors during pregnancy. Methods: Secondary analysis of prospective cohort data with 172 pairs (pregnant woman/fetus) treated at public health units. Anthropometric data, metabolic (glucose, glycated hemoglobin, insulin, insulin resistance, total cholesterol and fractions, triglycerides) measures, fetal biometry, and visceral and subcutaneous adiposity in the binomial (pregnant woman/fetus) were evaluated at the 16th, 28th and 36th gestational weeks by ultrasonography. Pearson's correlation coefficient and multiple linear regression were used, with a significance level of 5%. Results: At the 16th week, the mean age of the pregnant women was 26.6 ± 5.8 years and mean weight was 62.7 ± 11.5 kg; 47.0% had normal weight, 28.3% were overweight, 13.3% were underweight, and 11.2% were obese. At 36 weeks, 44.1% had inadequate gestational weight gain, 32.5% had adequate gestational weight gain, and 23.3% had excessive gestational weight gain. Fetal visceral adiposity at week 36 showed a positive correlation with maternal variables: weight (r = 0.15) and body mass index (r = 0.21) at the 16th; with weight (r = 0.19), body mass index (r = 0.24), and gestational weight gain (r = 0.21) at the 28th; and with weight (r = 0.22), body mass index (r = 0.26), and gestational weight gain (r = 0.21) at the 36th week. After multiple linear regression, adiposity at the 28th week remained associated with fetal variables: abdominal circumference (p < 0.0001), head circumference (p = 0.01), area (p < 0.0001), and thigh circumference (p < 0.001). At the 36th week, adiposity remained associated with the abdominal circumference of the 28th (p = 0.02) and 36th weeks (p < 0.001). Conclusion: Adiposity was positively correlated with the measurements of the pregnant woman. After the multivariate analysis, the persistence of the association occurred with the abdominal circumference, a central adiposity measurement with a higher metabolic risk. Resumo: Objetivo: Avaliar a adiposidade visceral fetal e fatores associados na gestação. Métodos: Análise secundária de dados de coorte prospectiva com 172 pares (gestantes/fetos) atendidas em unidades públicas de saúde. Foram avaliadas nas gestantes na 16a, 28a e 36a semana gestacional: medidas antropométricas, metabólicas (glicose, hemoglobina glicada, insulina, resistência à insulina, colesterol total e frações, triglicerídeos), biometria fetal e adiposidade visceral e subcutânea no binômio (gestantes/feto) por ultrassonografia. Utilizamos o coeficiente de correlação de Pearson e regressão linear múltipla, com nível de significância de 5%. Resultados: Na 16ª semana a média de idade das gestantes foi de 26,6 ± 5,8 anos e peso 62,7 ± 11,5 quilogramas, 47,0% eram eutróficas, 28,3% sobrepeso, 13,3% baixo peso e 11,2% obesas. Na 36a semana, 44,1% tiveram ganho ponderal gestacional insuficiente, 32,5% adequado e 23,3% excessivo. A adiposidade visceral fetal na 36a semana apresentou correlação positiva com variáveis maternas: peso (r = 0,15) e índice de massa corpórea (r = 0,21) na 16a; com peso (r = 0,19), índice de massa corpórea (r = 0,24) e ganho ponderal gestacional (r = 0,21) na 28a; com peso (r = 0,22), índice de massa corpórea (r = 0,26) e ganho ponderal gestacional (r = 0,21) na 36a semana. Após regressão linear múltipla a adiposidade na 28a semana permaneceu associada com variáveis fetais: circunferência abdominal (p < 0,0001), circunferência cefálica (p = 0,01), área (p < 0,0001) e circunferência da coxa (p < 0,001). Na 36a semana com circunferência abdominal da 28a (p = 0,02) e 36a semana (p < 0,001). Conclusão: A adiposidade foi positivamente correlacionada com medidas da gestante, após análise multivariada a persistência da associação deu‐se com a circunferência abdominal, medida de adiposidade central, de maior risco metabólico.